Ixekizumab for Psoriatic Arthritis: Safety, Efficacy, and Patient Selection - Miller J; Puravath AP; Orbai AM (Dove Medical Press, 2021)
John Miller,1,2 Abin P Puravath,1 Ana-Maria Orbai1,3 1Division of Rheumatology, Johns Hopkins University School of Medicine, Baltimore, MD, USA; 2Lyme Disease Research Center, Johns Hopkins University School of Medicine, Baltimore, MD, USA; 3Psoriatic Arthritis Program, Johns Hopkins University School of Medicine, Baltimore, MD, USACorrespondence: Ana-Maria OrbaiJohns Hopkins Division of Rheumatology, 5200 Eastern Avenue, MFL Center Tower Suite 4100, Baltimore, MD, 21043 Tel +1 410 550 8231Fax +1 410 550 2072Email aorbai1@jhmi.eduObjective: Ixekizumab is a monoclonal antibody targeting IL-17A and licensed for psoriasis, psoriatic arthritis (PsA) and axial spondyloarthritis. Review objectives were to summarize: 1) ixekizumab safety in people with PsA, 2) ixekizumab efficacy from Phase III randomized controlled trials, and 3) ixekizumab study participant PsA phenotypes.Methods: We conducted a search in PubMed limited to phase III randomized controlled trials (RCT) and corresponding long-term extension studies where the intervention was treatment with ixekizumab in a population with PsA.Results: We identified 17 publications and 13 met inclusion criteria. Injection site reactions (ISR) and allergic reactions occurred in up to 25.3% and 6.2% with ixekizumab and 4.5% and 1.85, respectively, with placebo. ISR occurred in 9.5- 10.6% at 24 and 52 weeks with ixekizumab versus 3.2- 3.5% with adalimumab (p < 0.01) in biologic-naïve PsA. Serious adverse events at 24 weeks occurred in 8.5% with adalimumab versus 3.5% with ixekizumab (p = 0.02), and at 52 weeks in 12.45 with adalimumab and 4.25 with ixekizumab (p < 0.01). Ixekizumab had similar efficacy to adalimumab across all PsA musculoskeletal, symptom and patient-reported outcome domains and surpassed adalimumab in psoriasis outcomes as well as all combined musculoskeletal and psoriasis outcomes. The study subject population was overwhelmingly white, balanced men-women, BMI at the obese threshold, had on average 7-year PsA duration and 15-year psoriasis duration. Disease activity was high with 7/66 swollen joints, 13/68 tender joints, 55% enthesitis, variable dactylitis (12- 51%), and active psoriasis in > 92%.Conclusion: Ixekizumab treatment in PsA was associated with a statistically significant higher risk of injection site reactions versus placebo or adalimumab. Ixekizumab had statistically significantly fewer serious adverse events than adalimumab. Ixekizumab demonstrated efficacy for all PsA disease activity domains as well as for slowing radiographic disease progression. The main shortcoming of the ixekizumab PsA program is lack of representation of African American study participants.Keywords: ixekizumab, psoriatic arthritis, interleukin-17 inhibitor, clinical trials, biologic therapy